Critical Thinking Skills through Industrial Revolution 4.0 for Vocational Education - Muhammad Ari Agung Wibowo; Sudji Munadi (Universitas Sultan Ageng Tirtayasa, 2020)
ABSTRACT Research is presented to map State Vocational High School (SMKN) in Boyolali based on Higher Order Thinking Skills (HOTS) owned by students. HOTS is indispensable in facing critical thinking skills in the 21st century. The research used uses a qualitative type of survey approach. Students in vocational schools are given cognitive questions oriented to HOTS which refers to Bloom's taxonomy, in the form of evaluating, analyzing, and creating. Questions are presented in multiple choice forms and have been validated with the questmaster program. The results showed that HOTS owned by students in Boyolali Vocational High School was still relatively low, ie 36% at SMKN 1 Klego, 37% in SMKN Nogosari, and 41% in students at SMKN 1 Klego.